Persepsi dan Makna Tradisi Perkawinan Bajapuik pada Masyarakat Sungai Garingging Kabupaten Padang Pariaman - Zike Martha (Universitas Airlangga, 2020)
Communication and culture is communication that has a reciprocal relarionship. Culture can influence communication and conversely communication affects culture and the prvailing culture in one area will be different from other regions. The Geringging River are, Padang Pariaman Regency. The Community has a tradition of giving japuik money in the custom of marriage. The marriage custom of Sungai Geringging In Padang Pariaman Regency is different from the marriage customs of other Minangkabau areas, becouse it has a Bajapuik tradition to pick up the groom) which requires japuik money. Many meaning are stroed fom this japuik money. Not all mean to demean or indeed buy someone. This is not a human trafficking transaction, just a culture to honor one’s partner in the way of the Garingging River community. This writing discusses and observes how the cultural communication of the meaning of the traditional of Bajapuik marriage in the Garinggiang River community Padang district. Using a Qualitative method with a descriptive design, namely writng that gives an accurate description of symptoms of particular individual or group of a situation and symptoms that occur, operationalizing the concept and producing variable and indicators. Basically, every community in their life will experience changes, changes are condition of a community at diferent times and places, as well as the implementation of the Bajapuik tradition in the Garinggiang River.